Naturaleza y americanidad en "Altazor" de Vicente Huidobro - López, Alejo (2014)
Part of the Latin American criticism built on Vicente Huidobro's figure the image of a French poet from his condition of bilingual writer, and especially from the unavoidable frame of the European Avant-gardein which most of his work inscribes. More than sixteen years in Europe, his participation in the avant-garde circles and, especially, a work that wanders freely between French and Spanish, make of Huidobro an erran tfigure, a writer between borders that hinders any submission to categories as those of nationality or language. From these crossroad established by his work and its critical reception we propose to analyze Altazor, one of Huidobro's most consecrated poems, in order to show how the poem is governed by a Latin American stamp that identifies the experience of Nature as maximum genesic force with the American space. This americanity based on the driving (in his Freudian meaning of Trieb) nature of the continent appears in Huidobro ́s work directly opposed to the funereal space of postwar Europe, and turns, therefore, into the perfect place to face up the creationist task of his poetry.